Congenital Trifurcation of the Trachea - Kiarash Taghavi; David Perry; James K. Hamill (Georg Thieme Verlag KG, 2014)
Abstract "Tracheal trifurcation" is a veritable and rare finding. We illustrate a unique case that demonstrates the complexity and broad variability that congenital tracheobronchial anomalies can take. Appreciation of these is important at intubation, bronchoscopy, and surgery.